Penguatan Pendidikan Karakter Berbasis Mushalla sebagai Bentuk Melestarikan Kearifan Lokal - Agus Readi (Edukais : Jurnal Pemikiran Keislaman, 2022)
Building the character of students is the essence of education itself. Both characters related to God (spiritual), with oneself, with others, with the environment and with nationality. This study uses a qualitative approach. Data collection techniques through interviews, observation and documentation. Data analysis techniques through data reduction, presentation and conclusion. The results of the research are: 1) strengthening character education includes spiritual aspects, social aspects and environmental aspects; 2) the constraints faced include internal and external factors